INSTITUIONAL AND LEGAL BASIS OF THE DEVELOPMENT OF THE INTERNATIONAL RELAIONS BETWEEN STATES OF THE CARPATHIAN EUROREGION - Мітряєва, С.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Analysis of collaboration should begin with the definition of institutional and legal framework. The international legal framework – is the foundation upon which the whole system of foreign relations is built. Neighboring countries of Ukraine ( Carpathian Euroregion partners ) are already members of the EU supranational union , so in addition to the analysis of the power of each of the aforementioned countries , should take into account the capacity of the EU, which creates „additional capacity" for its members.